Differential effect of NAT2 on the association between active and passive Smoke exposure and breast cancer risk - Chang-Claude, Jenny; Kropp, Silke; Bartsch, Helmut; Risch, Angela (Cancer epidemiology, biomarkers & prevention, 2002)
Background: Polymorphisms in the N-acetyltransferase 2 (NAT2) gene influence the rate of metabolism of aromatic and heterocyclic amines present in tobacco smoke. Because the physicochemical composition of mainstream and sidestream smoke differ, we conducted a case-control study to assess a possible differential effect of NAT2 genotype on the relationship between active/passive smoke exposure and breast cancer risk. Methods: Breast cancer patients diagnosed by 50 years of age and population-sampled controls were interviewed to obtain detailed lifetime active and passive smoking history. NAT2 genotype was determined in 422 breast cancer patients and 887 controls. Multivariate logistic regression analysis was performed to estimate breast cancer risk in relation to smoking history by acetylator status and interaction effects. Results: Compared with women never regularly exposed to tobacco smoke, odds ratios (ORs) for current smoking and ex-smoking were 1.7 [95% confidence interval (CI): 1.0-2.9] and 1.2 (95% CI, 0.7-2.0) in slow acetylators, and not increased in rapid acetylators. Active smoking variables, such as pack-years, duration of smoking, and time since cessation, showed significant dose-response relationships with breast cancer risk among slow acetylators but not rapid acetylators. In contrast, passive smoking was associated with higher risk in rapid than in slow acetylators, with ORs of 2.0 (95% CI, 1.0-4.1) and 1.2 (95% CI, 0.7-2.0), respectively. Conclusions: Our results suggest that the NAT2 status has a differential effect on the association of active and passive smoking with breast cancer and demonstrate the need to consider possible different mechanisms associated with exposure to main- and sidestream tobacco smoke.